Islamic Law and National Law (Comparative Study of Islamic Criminal Law and Indonesian Criminal Law) - Moh. Yasir; Joko Widodo; Ali Ashar (Alhurriyah, 2022)
The Indonesian state, although the country is not an Islamic state, but in terms of Islamic legal values, both partially and completely, which are the substantive norms in various laws and regulations in Indonesia, such as the Marriage Law, Waqf Law, Hajj Law, Banking Law (both Law No. /1998 as well as Law 21/2008). The Islamic criminal law that has been implemented is in the Province of Aceh Darus Salam, which is only a small part. This study aims to determine the description of Islamic law, Islamic criminal law, and to determine the purpose of Islamic law and Indonesian criminal law. This study uses a qualitative method with a normative juridical approach. The results of the study indicate that Islamic law is a set of regulations based on the revelation of Allah and the sunnah of His Messenger regarding the behavior of the mukallaf human which is recognized and believed to be valid and binding for all Muslims who are Muslims with legal sources or arguments originating from the Qur'an, Sunnah Prophet, and Ra'yu/ Ijtihad. While Islamic criminal law is the law that regulates crime and its sanctions, with the aim of preserving human life in their religion, themselves, their minds, their assets, their honor and the relationship between the perpetrators of crimes, victims and society. Islamic law itself aims to realize or realize and maintain the benefit of humans in this life (world) in order to obtain happiness in this world and in the hereafter. Meanwhile, Indonesian criminal law aims to prevent crimes and violations of the law and provide a deterrent effect for perpetrators of criminal acts.Negara Indonesia walaupun negaranya bukan bentuk negara Islam , namun secara nilai-nilai hukum islam baik sebagian maupun seluruhnya yang menjadi norma substantif dalam berbagai peraturan perundang-undangan di Indonesia seperti hal UU perkawinan, UU Wakaf, UU Haji, UU Perbankan (baik UU No 10/1998 maupun UU 21/2008). Adapun hukum pidana Islam yang sudah menerapkan adalah di Provinsi Aceh Darus Salam yang baru sebagian kecil saja. Penelitian ini bertujuan untuk mengetahui gambaran hukum Islam, hukum pidana Islam, dan untuk mengetahui tujuan hukum Islam serta hukum pidana Indonesia. penelitian ini menggunakan metode kualitatif dengan pendekatan yuridis normatif. Hasil penelitian menunjukkan bahwa hukum Islam adalah seperangkat peraturan berdasarkan wahyu Allah dan sunnah Rasul-Nya mengenai perilaku manusia mukallaf yang diakui dan diyakini sah dan mengikat bagi seluruh umat Islam yang beragama Islam dengan sumber atau dalil hukum yang bersumber dari Al-Qur'an, Sunnah Nabi. , dan Ra'yu/ Ijtihad. Sedangkan hukum pidana Islam adalah hukum yang mengatur tentang kejahatan dan sanksinya, dengan tujuan untuk memelihara kehidupan manusia dalam agamanya, dirinya, akalnya, hartanya, kehormatannya dan hubungan antara pelaku kejahatan, korban dan masyarakat. . Hukum Islam sendiri bertujuan untuk mewujudkan atau mewujudkan dan memelihara kemaslahatan manusia dalam kehidupan (dunia) ini agar memperoleh kebahagiaan di dunia dan di akhirat. Sedangkan hukum pidana Indonesia bertujuan untuk mencegah terjadinya kejahatan dan pelanggaran hukum serta memberikan efek jera bagi pelaku tindak pidana.